2009
DOI: 10.4049/jimmunol.0901539
|View full text |Cite
|
Sign up to set email alerts
|

TCR Down-Regulation Controls T Cell Homeostasis

Abstract: Material

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

3
10
0

Year Published

2011
2011
2022
2022

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 13 publications
(13 citation statements)
references
References 62 publications
3
10
0
Order By: Relevance
“…This phenomenon is of particular relevance when redirecting T cells with defined specificity towards target cells. While reduced response of early-stage CD45RO + T cells is due to down-regulated expression of TCR components, especially the CD3-gamma chain, following ligand triggering [19], we here revealed that T cells in more differentiated stages, in particular in the KLRG-1 −/low CD57 − CD7 + intermediate and KLRG-1 + CD57 + CD7 − late-stage of terminal differentiation, express the TCR and bind specific tetramers with similar efficiencies; CD7 − T cells, however, respond less efficiently with IFN-gamma and cytolytic degranulation than the CD7 + KLRG-1 −/low CD57 − T cells. While hypo-responsiveness of intermediate-stage T cells is due to blockade through PD-1/PD-1L interaction, this is not the case for late-stage T cells (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…This phenomenon is of particular relevance when redirecting T cells with defined specificity towards target cells. While reduced response of early-stage CD45RO + T cells is due to down-regulated expression of TCR components, especially the CD3-gamma chain, following ligand triggering [19], we here revealed that T cells in more differentiated stages, in particular in the KLRG-1 −/low CD57 − CD7 + intermediate and KLRG-1 + CD57 + CD7 − late-stage of terminal differentiation, express the TCR and bind specific tetramers with similar efficiencies; CD7 − T cells, however, respond less efficiently with IFN-gamma and cytolytic degranulation than the CD7 + KLRG-1 −/low CD57 − T cells. While hypo-responsiveness of intermediate-stage T cells is due to blockade through PD-1/PD-1L interaction, this is not the case for late-stage T cells (unpublished data).…”
Section: Discussionmentioning
confidence: 99%
“…For murine FACS analyses of cell surface and intracellular molecules, we used antibodies against CD8 (53-6.7), TCRVβ8 (F23.1), TCRVα2 (B20.1), CD62L (MEL-14), CD44 (IM7), IFN-γ (XMG1.2), and TNF-α (MP6.XT22) all from BD Biosciences, granzyme B (GB11, Invitrogen) and perforin (eBioOMAK-D, eBioscience). For phenotyping, cells from thymus, spleen, and LNs were isolated, stained with antibodies against CD4 (RM4-5), CD8 (53-6.7), TCRVα2 (B20.1), and CD19 (1D3) from BD Biosciences, and analyzed by FACS as previously described [44]. For CD107a staining CTLs were restimulated for the time indicated with 100 ng/mL gp [33][34][35][36][37][38][39][40][41] in the presence of CD107a-FITC antibody (1D4B from BD Biosciences) and 3 μM monensin as previously described [29].…”
Section: Expansion Of T Cells and Facs Analysismentioning
confidence: 99%
“…Thus, during the steady state, TCR molecules transit through a recycling pool, as a result of internalization, endocytosis and cycling from and to the plasma membrane, via vesicular transport (Clark and Griffiths, 2003; Das et al, 2004; Liu et al, 2000; Minami et al, 1987; Myers et al, 2005). It has been speculated that constant TCR recycling during the steady-state, together with other biochemical events, contribute to control T cell homeostasis (Boding et al, 2009). In addition, the rapid cycling of surface receptors allows T cells to respond rapidly to stimuli by controlling responsiveness to peptide/MHC ligands (Harding and Unanue, 1990).…”
Section: Discussionmentioning
confidence: 99%